Leveraging Financial Statement Audits for Strategic Business Insights - Safira, Putri Ayu (Advances: Jurnal Ekonomi & Bisnis, 2023)
The purpose of this study is to explore the strategic implications of leveraging financial statement audits for organizational decision-making and performance enhancement. Through a comprehensive literature review, the research design and methodology involved systematic analysis of existing literature to identify key themes, concepts, and empirical findings related to the strategic utilization of audits. Findings reveal the evolution of financial statement audits from traditional compliance tools to strategic assets, driven by technological advancements, regulatory reforms, and changing stakeholder expectations. Implications suggest that organizations can enhance decision-making processes, mitigate risks, and seize opportunities by investing in audit capabilities and technologies, fostering collaboration, and adopting proactive audit planning approaches. The synthesis of findings highlights significant opportunities for further research, including exploration of specific audit methodologies, governance structures, ethical challenges, and audit education initiatives. The study underscores the importance of continued research efforts and collaboration to advance knowledge and practice in leveraging financial statement audits for strategic business insights, enabling organizations to thrive in today's complex and dynamic business environment.